First experimental survey of Chlamydia abortus in the genital tract of cows slaughtered in Algeria - Radja Zineddine; Djamila Hezil; Hassane Benseghir; Garigliany, Mutien; Ghalmi, Farida (International Journal of Computational and Experimental Science and Engineering, 2025)
The analysis of samples from the genital tract of slaughtered cattle allows for the assessment of the impact of infections on reproduction. Among the agents involved, Chlamydiaceae are known for their role in these diseases.The objective of this study was to investigate the presence of Chlamydia abortus in the reproductive tract of cull cows and to explore the potential correlation between the presence of apparent morphological lesions in the genital tract and the carriage of the bacteria.Macroscopic examination of 405 female bovine genital tracts collected from abattoirs in eastern Algeria revealed a 7.16% prevalence of apparent morphological abnormalities, with ovarian lesions predominating. Real-time PCR analysis of tissue samples taken from the genital tract of cows aimed at detecting the DNA of Chlamydia abortus targeting a fragment of the ompA gene, revealed no trace of the bacterium in the tissue samples analysed.The results suggest the occasional presence of the bacterium in the genital tract of female cattle and call into question the hypothesis that cows act as a reservoir for Chlamydia abortus.